Cycling Underrepresented in EU Member States Final National Energy and Climate Plans. - Küster, Fabian; Watson, Maya (My University, 2020)
In the European Green Deal, released late 2019, the Commission announced its decarbonization objective: no net emissions of greenhouse gases by 2050. To achieve this objective, transport emissions must be reduced by 90% by 2050 compared to 1990. Because the National Energy and Climate Plans(NECPs) are among the EU’s primary methods to meet its climate goals, these plans must include bold transport decarbonization measures. There is no conceivable way for the EU to achieve decarbonization without a major, further shift towards more cycling. In fact, a Global High Shift scenario with an emphasis on cycling and e-cycling could cut CO2 emissions from urban transport by nearly 7% by 2030. To achieve zero-carbon emissions across Europe by 2050, it is therefore vital that European countries strongly support and fund cycling. To determine the role of cycling, the study assesseds the 27 draft and final NECPs 2021 – 2030. It founds that the attention given to cycling has improved since the (2018) draft NECPs: from a draft score of 2.7/10, the final NECPs scored 4.35/10. However, many Member States still did not add enough measures to support or fund cycling. This moderate score shows that Member States have begun to take the decarbonization potential of cycling seriously, but there is still a long way to go. Cycling must be considered a necessary tool to decarbonize road transport. ECF analysis also shows a discrepancy in certain national policy frameworks (National cycling strategies, national climate laws) where considerable higher attention has been paid to cycling than in their NECP.
Keywords: Fahrradverkehr; Nachhaltige Verkehrsentwicklung; Verkehrspolitik; Klimapolitik; Emissionsminderung; Internationaler Vergleich; Radverkehrsförderung